Beyond Moral Commitment and Binding Force: A Spectrum-Based Analysis of Memoranda of Understanding in Indonesian Contract Law - Astrid Salfa; Sudirman; Ma’ruf Akib (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
Memoranda of Understanding (MoUs) are widely used in governmental and commercial practice in Indonesia, yet their legal status remains contested due to the absence of explicit regulation in the Indonesian Civil Code. This article examines the legal position of MoUs within Indonesian contract law by analyzing their normative foundations under freedom of contract, pacta sunt servanda, and their role in the pre-contractual phase. Employing a normative juridical method with doctrinal and comparative analysis, the study argues that the binding force of an MoU cannot be determined by its formal label but must be assessed based on the substantive allocation of rights and obligations, the parties’ intention to create legal relations, and compliance with Article 1320 of the Civil Code. The findings demonstrate that MoUs operate along a legal spectrum, ranging from non-binding moral commitments to instruments capable of generating contractual liability. By advancing a spectrum-based framework, this article contributes to contract law scholarship and provides normative guidance for courts and practitioners in drafting, interpreting, and enforcing MoUs.